EFFECTIVE CATALYSTS FOR THE SELECTIVE RESTORATION OF AROMATIC MONO- AND DINITRO COMPOUNDS - Larissa R. Sassykova,; Nariman E.Maximov,; Arman Y. Yerzhanov,; Madina S. Ilmuratova,; Abdolla T. Raiyssov,; Yermek A. Aubakirov,; Ryskul N. Azhigulova,; Aigul A. Batyrbayeva,; Subramanian Sendilvelan, (Academic Scientific Journal of Chemistry, 2020)
This article discusses the issues of catalytic reduction of aromatic nitro compounds to obtain valuable intermediate and final products-aromatic amines. The most important method for producing amines from nitro compounds is catalytic reduction with hydrogen on catalysts. The article describes in detail the choice of catalysts for hydrogenation of nitro compounds at atmospheric and high hydrogen pressure. Studies of hydrogenation reactions of aromatic nitro compounds on nickel, copper and iron catalysts are discussed. Hydrogenation of aromatic nitro compounds on catalysts based on palladium, platinum, and rhodium deposited on various carriers, including nanodiamonds, is considered. Catalysts based on supported palladium catalysts with copper additives showed high selectivity in the hydrogenation of nitro groups in nitro compounds with functional groups; and with the addition of platinum and rhodium, during the reduction of both nitro groups and the aromatic ring in nitrobenzene. In the works on the use of nanodiamonds, it was found that catalysts based on platinum and palladium nanoparticles of 4-5 nm in size, fixed on nanodiamonds, were highly active in liquid-phase hydrogenation reactions of nitro compounds under mild conditions. The data described by the authors on theoretical issues and practical problems of catalytic hydrogenation of aromatic nitro compounds are very relevant. The article is based on the analysis of domestic and foreign literature and may be useful to specialists in the field of catalysis.